Effects of Square-Stepping Exercise on cognitive function in early geriatric rehabilitation: A randomized controlled explorative study - Katja Fränzel; Jessica Koschate-Storm; Ellen Freiberger; Ryosuke Shigematsu; Tania Zieschang; Svenja Tietgen (PLoS ONE, 2026)
Objectives The aim of the explorative study was to evaluate the effect of Square-Stepping Exercise (SSE) on cognitive function compared to conventional physiotherapy (cPT) in early geriatric rehabilitation. A training effect of SSE on cognitive function particularly on executive functions was expected. Methods This explorative study was conducted in the department of early geriatric rehabilitation in a general hospital. Fifty-eight inpatients (27 female), with a median age of 79.1 (range: 63–90) were randomized to the control group (CG, n = 29) or the intervention group (IG, n = 29). CG received cPT five days per week during their hospital stay. For the IG, SSE replaced cPT for at least six sessions throughout the hospital stay, alternating with cPT. Executive function was assessed via the test battery for attentional performance (TAP), memory function was evaluated using the digit span test. Results Both groups improved in the divided attention task (total pre 9.9 missing items; total post 7.5 missing items, p = 0.011), and in the flexibility task (total pre 2034.49 ms; total post 1680.60 ms, p = 0.004). There was no specific training effect of SSE on executive functions measured with the TAP. No improvement in memory function was noted in either group. Conclusion Inpatients receiving SSE combined with cPT improved similarly in cognitive domains during early geriatric rehabilitation compared with inpatients offered cPT alone. SSE can be used as an additional component in early geriatric rehabilitation, which due to its playful characteristics might be more motivational or intriguing for some inpatients. Trial registration ClinicalTrials.gov DRKS00026191